Deep cryptic diversity in the Craugastor podiciferus Species Group (Anura: Craugastoridae) of Isthmian Central America revealed by mitochondrial and nuclear data - Erick Arias; Andrew J. Crawford; Andreas Hertz; Gabriela Parra Olea (PeerJ)
The Craugastor podiciferus Species Group contains eleven species of terraranan frogs distributed from eastern Honduras to eastern Panama. All species have remarkable color pattern polymorphisms, which may contribute to potential taxonomic problems. We performed exhaustive sampling throughout the geographic distribution of the group to evaluate the phylogenetic relationships and biogeographic history of all named species based on two mitochondrial markers and nuclear ddRAD loci. We also implemented various species delimitation methods to test for the presence of unconfirmed candidate species within the group. Molecular phylogenetic analyses showed that the group contains four major clades. All currently named species are supported by molecular data, yet species richness within the group is clearly underestimated. Species delimitation was discordant between the mitochondrial and nuclear datasets and among analytical methods. Adopting a conservative approach, we propose that the C. podiciferus species group contains at least 12 unconfirmed candidate species. Ancestral area reconstruction showed that the group originated and diversified in the highlands of the Talamancan montane forest ecoregion of Costa Rica and western Panama.